2021
DOI: 10.1111/jfbc.13810
|View full text |Cite
|
Sign up to set email alerts
|

Cassia auriculata leaf extract ameliorates diabetic nephropathy by attenuating autophagic necroptosis via RIP‐1/RIP‐3‐p‐p38MAPK signaling

Abstract: Diabetic nephropathy (DN) is the most common manifestation of high glucose induced diabetes mellitus. In this study, we report the effects of Cassia auriculata ethanol leaf extract (CALE) on DN‐associated cell toxicity and complications. The effects of CALE were screened in vitro using RGE cells. Cell viability was assessed using MTT and flow cytometry. Male Sprague‐Dawley rats were divided into control, DN and treatment groups (n = 8). The DN and treatment groups received 60 mg/kg/bw of streptozotocin in citr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
(34 reference statements)
1
2
0
Order By: Relevance
“…Xu et al found that upregulation of UCHL1 in podocytes of DN patients increased the de-ubiquitination of RIPK1 and RIPK3, thereby facilitating the necroptosis of podocytes 25) . Shahrani et al also demonstrated that necroptosis was involved in podocyte injury induced by HG in vitro 11) , which is consistent with the results of the present study. Except for cell injury, detachment is considered as another contributor to the decrease of podocyte density 26) .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Xu et al found that upregulation of UCHL1 in podocytes of DN patients increased the de-ubiquitination of RIPK1 and RIPK3, thereby facilitating the necroptosis of podocytes 25) . Shahrani et al also demonstrated that necroptosis was involved in podocyte injury induced by HG in vitro 11) , which is consistent with the results of the present study. Except for cell injury, detachment is considered as another contributor to the decrease of podocyte density 26) .…”
Section: Discussionsupporting
confidence: 93%
“…Recently, USP22 was demonstrated to drive necroptotic cell death by reducing RIPK3 ubiquitination 10) . Importantly, a growing number of studies over the last decade found that necroptosis was observed in DN 11,12) . In addition, multiple experimental data suggested that USP22 plays a regulatory role in DN progression, which may be a promising target for DN 13,14) .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the traditional Chinese medicine drugs could inhibit necroptosis such as aucubin, 221 wogonin, 222 patchouli alcohol, 223 and cassia auriculata leaf extract. 224 In conclusion, drugs and agents that inhibit necroptosis or the expression of RIPK1, RIPK3, and MLKL may have therapeutic potential for human disease.…”
Section: Drugs and Agents That Regulate Necroptosismentioning
confidence: 98%